Modelling road space prioritisation for public transport using AIMSUN: a case study in Durban - Moodley, Lavern (Department of Civil Engineering, 2017)
This study exhibits road space prioritisation of three types of public transport systems. The study first goes into a literature review of road space prioritisation and aspects of modelling this. These types of systems were then modelled using a case study of a single corridor in Durban, South Africa. Both a macroscopic modelling and microscopic modelling package were used to model a base year and various public transport scenarios. This was done to illustrate the effects of road space prioritisation along a corridor of the city. The three public transport scenarios performed were: a quality bus scenario, a bus rapid transit system scenario and a mini-bus -taxi scenario. For a certain purpose, a relationship in road capacity could be formed between the macroscopic model and the microscopic model. A costing analysis of these three scenarios was done at the end of the results chapter. It was concluded that the bus rapid transit system was the most feasible public transport system for the corridor based on the demand pattern used in this study for that specific corridor.